Deep Learning-Based Raudhatul Athfal Curriculum Transformation for Strengthening Early Childhood Islamic Values - Khotimatul Majidah S; Fatimatul Hotimah; Dairina Yusri; Amar Tarmizi; Nikmatur Ridha (The Islamic Education and Multiculturalism Foundation, 2026)
AbstrakPenelitian ini bertujuan menganalisis transformasi implementasi kurikulum Raudhatul Athfal berbasis pembelajaran mendalam dalam penguatan nilai-nilai keislaman anak usia dini di RA Ar Rum Medan Marelan. Fokus penelitian diarahkan pada perubahan perencanaan kurikulum, pelaksanaan pengalaman belajar, strategi internalisasi nilai keislaman, asesmen perkembangan anak, serta faktor pendukung dan penghambat implementasinya. Penelitian dirancang menggunakan pendekatan kualitatif dengan jenis studi kasus. Data diperoleh melalui observasi kegiatan pembelajaran, wawancara semi-terstruktur dengan kepala RA, guru, dan orang tua, serta analisis dokumen kurikulum, modul ajar, media pembelajaran, dan catatan perkembangan anak. Data dianalisis melalui proses kondensasi data, penyajian data, penarikan kesimpulan, dan verifikasi, sedangkan keabsahannya diperkuat melalui triangulasi sumber, teknik, dan waktu. Secara analitis, penelitian ini menguji transformasi kurikulum melalui keterpaduan pembelajaran berkesadaran, bermakna, dan menggembirakan dengan penanaman keimanan, ibadah, akhlak, kasih sayang, tanggung jawab, dan kepedulian sosial. Hasil akhir penelitian diharapkan menghasilkan model implementasi kurikulum RA yang tidak hanya menekankan pembiasaan ritual, tetapi juga membantu anak memahami, mengalami, dan merefleksikan nilai-nilai Islam dalam kehidupan sehari-hari.Kata Kunci: Pembelajaran Mendalam; Kurikulum Raudhatul Athfal; Nilai Keislaman; Anak Usia Dini; Transformasi Kurikulum. Abstract This study aims to analyze the transformation of deep learning-based curriculum implementation in strengthening Islamic values among young children at Raudhatul Athfal Ar Rum, Medan Marelan. The study focuses on changes in curriculum planning, the implementation of learning experiences, strategies for the internalization of Islamic values, assessments of children’s development, and the supporting and inhibiting factors affecting implementation. This study employs a qualitative approach with a case study design. Data were collected through observations of learning activities, semi-structured interviews with the principal, teachers, and parents, as well as analyses of curriculum documents, teaching modules, instructional media, and children’s developmental records. The data were analyzed through data condensation, data display, conclusion drawing, and verification, while the trustworthiness of the findings was strengthened through source, methodological, and time triangulation. Analytically, this study examines curriculum transformation through the integration of mindful, meaningful, and joyful learning with the cultivation of faith, worship practices, moral character (akhlak), compassion, responsibility, and social awareness. The study is expected to produce a model for implementing the Raudhatul Athfal curriculum that not only emphasizes the habituation of religious rituals but also enables children to understand, experience, and reflect upon Islamic values in their everyday lives. Keywords: deep learning; Raudhatul Athfal curriculum; Islamic values; early childhood; curriculum transformation